A Case of Intense Pulsed Light Aggravated Rosacea Successfully Treated by Abrocitinib - Mao L; Xiong L; Deng Y; Xiong X (Clinical, Cosmetic and Investigational Dermatology, 2025)
Lan Mao,1 Ling Xiong,1 Yongqiong Deng,2 Xia Xiong1 1Department of Dermatology, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 2Department of Dermatology, Chengdu Integrated Traditional Chinese and Western Medicine Hospital, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Xia Xiong, Email xiongxia789@126.com Yongqiong Deng, Email dengyongqiong1@126.comAbstract: Rosacea is a chronic inflammatory skin condition characterized by facial erythema, papules, pustules, telangiectasia, and flushing. Currently, various treatment options are available, but no definitive cure has been established. Phototherapy is primarily effective for treating telangiectatic rosacea because it helps alleviate erythema and telangiectasia. However, it can also pose risks; when applied inappropriately, phototherapy may worsen rosacea symptoms, making the condition more difficult to manage. This case report presents a patient with rosacea who experienced acute exacerbation after intense pulsed light therapy, characterized by persistent erythema, edema, pustules, exudation, and a burning sensation with pain. Subsequent treatment with oral abrocitinib for 12 weeks led to a gradual resolution of the patient’s facial symptoms. Therefore, we hypothesized that the oral JAK-1 inhibitor abrocitinib not only serves as a promising new treatment option for rosacea but also offers therapeutic benefits in cases of inappropriate phototherapy.Keywords: rosacea, intense pulsed light, JAK inhibitor, abrocitinib